2000
DOI: 10.1093/humrep/15.suppl_1.81
|View full text |Cite
|
Sign up to set email alerts
|

Uterine contractility during the menstrual cycle

Abstract: The non-pregnant uterus shows different patterns of contractility during the menstrual cycle. A renewed interest in uterine contractility has resulted from reports of non-invasive ultrasound (US) based studies. To clarify the changes in uterine contractility occurring throughout the menstrual cycle, we prospectively studied uterine contractions (UC) at six representative stages with US and intrauterine pressure (IUP) based approaches in 30 cycling volunteers. Results showed UC frequency could be measured by ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 16 publications
6
142
0
6
Order By: Relevance
“…The maximum amplitudes of transverse cavity centerline movement were 0.5-1.5 mm with a mean ± SD of 0.94 ± 0.34 mm. 7 Proliferative TVS 0.6-5.4 Bulletti et al 12 Proliferative: Catheter + TVS late follicular 2.70 ± 0.6 periovulatory 3.50 ± 0.6 Nakai et al 13 Proliferative MRI 2.82 Present study Proliferative and early secretory TVS 2.94 ± 0.6 *Data given as range, mean or mean ± SD. MRI, magnetic resonance imaging; TVS, transvaginal sonography.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The maximum amplitudes of transverse cavity centerline movement were 0.5-1.5 mm with a mean ± SD of 0.94 ± 0.34 mm. 7 Proliferative TVS 0.6-5.4 Bulletti et al 12 Proliferative: Catheter + TVS late follicular 2.70 ± 0.6 periovulatory 3.50 ± 0.6 Nakai et al 13 Proliferative MRI 2.82 Present study Proliferative and early secretory TVS 2.94 ± 0.6 *Data given as range, mean or mean ± SD. MRI, magnetic resonance imaging; TVS, transvaginal sonography.…”
Section: Resultsmentioning
confidence: 71%
“…This study included 18 healthy non-pregnant women aged 28-41 years (12 of whom were 35 years or older) who had anatomically normal uteri and were in the proliferative (15 women at days [10][11][12][13][14] or early secretory (three women at days 15-18) phase of their menstrual cycle. The study was approved by the hospital ethics committee and all women gave written informed consent to participate.…”
Section: Methodsmentioning
confidence: 99%
“…The uterus, unlike the brain, for instance, undergoes constant small movements due to normal breathing and spontaneous uterine contractions (Bulletti et al, 2000). Because these effects can lead to poor MR measurements using DTI, data were obtained from five ex vivo organs of patients aged between 34 and 61 years subjected to hysterectomy for medical reasons.…”
Section: Materials and Methods Organ Acquisition And Embeddingmentioning
confidence: 99%
“…Buletti et al [7] injected specimens with coloured latex and noted that venous vessels can form large dilatations -the so called 'venous lakes'. He found that they are more numerous at early and midluteal phases.…”
Section: Discussionmentioning
confidence: 99%
“…Bulletti et al [7] stated that the most important morphological changes occur on spiral and arcuate arteries, as well as on venous lakes. Further data on the morphology and variations of the venous lakes, using SEM, should be acquired.…”
Section: Discussionmentioning
confidence: 99%